Healthy Eating: Calcium - Linda B. Bobroff (EDIS)
Revised! FCS8568, a 2-page illustrated handout by Linda B. Bobroff, uses a question-and-answer format to provide key information for elders about what calcium is, what foods contain it, what happens when people do not get enough, and how much older adults need. Published by the UF Department of Family Youth and Consumer Sciences, March 2010.